2016
DOI: 10.1158/2159-8290.cd-15-0854
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Expression of miR-143/145 Promotes Neoangiogenesis in Lung Cancer Development

Abstract: The two unrelated miRNAs, miR-143 and miR-145, co-expressed from the miR-143/145 cluster have been proposed to act as tumor suppressors in human cancer and therapeutic benefits of delivering miR-143 and miR-145 to tumors have been reported. In contrast, we found that tumor-specific deletion of miR-143/145 in an autochthonous mouse model of lung adenocarcinoma did not affect tumor development. This was consistent with the lack of endogenous miR-143/145 expression in normal and transformed lung epithelium. Surpr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
116
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(130 citation statements)
references
References 45 publications
6
116
1
Order By: Relevance
“…Various studies and recent publications indicate that miR‐145 plays a role in cell proliferation, migration, and invasion in PCa and correlates with a high Gleason score, PSA, and bone metastasis . Other recent studies have shown that miR‐145 is involved with stromal‐related genes, as opposed to those related to the epithelium . In our study, miR‐145 expression could be from both cancer and stromal genes.…”
Section: Discussionsupporting
confidence: 62%
“…Various studies and recent publications indicate that miR‐145 plays a role in cell proliferation, migration, and invasion in PCa and correlates with a high Gleason score, PSA, and bone metastasis . Other recent studies have shown that miR‐145 is involved with stromal‐related genes, as opposed to those related to the epithelium . In our study, miR‐145 expression could be from both cancer and stromal genes.…”
Section: Discussionsupporting
confidence: 62%
“…Primary tumors were graded by a pathologist (R. Bronson) following established criteria (42), and only advanced (grades 3 and 4) tumors were used for the analysis. For the transplantation studies, 10 5 KP tumor cells (1233 line) (43) were injected via the lateral tail vein into mice or 5 × 10 5 KP tumor cells were injected s.c.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that stromal expression of miR-145 could promote neoangiogenesis in lung cancer development (5). miR-145 has also been suggested as one of the predictive factors for the early prediction of lymph node metastasis in patients with hepatocellular carcinoma (6).…”
Section: Disscussionmentioning
confidence: 99%
“…Both in vitro and in vivo studies have shown that miR-145 can significantly inhibit proliferation, migration and invasion in cancer cells (4). However, it has recently been found that tumor-specific deletion of miR-145 in an autochthonous mouse model of lung adenocarcinoma did not affect tumor development, and that stromal expression of miR-145 promotes neoangiogenesis in lung cancers (5), thus arguing against the delivery of this miRNA as an agent in cancer therapeutics. Moreover, miR-145 displays dramatic up-regulation in hepatocellular carcinoma and colorectal cancers with lymph node metastasis in comparison to those without lymph node metastasis (6, 7), suggesting that miR-145 may promote lymph node metastasis of cancer, or it may even play an oncogene role in metastatic cancer.…”
Section: Introductionmentioning
confidence: 99%